The Eskimo of Siberia. Memoirs of the AMNH - Bogoras, Waldemar, 1865-1936 (Leiden, E. J. Brill ltd.; New York, G. E. Stechert & co., 1913)
p. 417-456 36 cm. Folk-tales.--Songs.--Text: The one-who-finds-nothing.